FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPEMILIKAN AKTA KELAHIRAN DI DESA SUMPU KECAMATAN HULU KUANTAN KABUPATEN KUANTAN SINGINGI - Bidara Tania Gumilang; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Based on the data of Pusat Statistik Kuantan Singingi, from the year 2012-2014 there were 221 140 inhabitants the number of births, but only 114 671 inhabitants who take care of the birth certificate. Public awareness in possession of a birth certificate in the Desa Sumpu Kecamatan Hulu Kuantan Kabupaten Kuantan Singingi. Community considers that “birth certificate” is not an essential requirement in life.The problem in this research are; What are the Factors that Affect Birth Certificates in the Desa Sumpu Kecamatan Hulu Kuantan Kabupaten Kuantan Singingi ?. This type of research in this paper by using descriptive qualitative data collection techniques in research, among others; interviews, observation, literature study and documentation. Sources of data in this study are primary data and secondary data.Based on the results of research conducted that the first factor; public awareness of the importance of birth certificates for children ananya along with their birth certificates will are conducive ditertib administration and will facilitate their children to continue their education. The second factor; because the public administration burdened with many requirements to take care of a birth certificate, birth certificate due to the care of the society must stop working three days for the sakta menguru. The third factor; limited access to much of people's homes with the Office of Civil Registry and make people have no desire to do the maintenance of a birth certificate, as well as the duration of the process to obtain the deed of births who need 60 working days by the Department of Population and Civil Registration. The cost factor of transport to get to ibukotaka regency require substantial funds, to one way only they need money for transport of one hundred thousand rupiah (Rp. 100,000.00).Keywords: Factors, Ownership, Akta Kelahiran